Seasonal changes in steroid and thyroid hormone content in shed skins of the tegu lizard Salvator merianae - Zena, Lucas A. [UNESP]; Dillon, Danielle; Hunt, Kathleen E.; Navas, Carlos A.; Bícego, Kênia C. [UNESP]; Buck, C. Loren (Springer Nature, 2022)
Sampling blood for endocrine analysis from some species may not be practical or ethical. Quantification of hormones extracted from nontypical sample types, such as keratinized tissues, offers a less invasive alternative to the traditional collection and analysis of blood. Here, we aimed to validate assays by using parallelism and accuracy tests for quantification of testosterone, corticosterone, progesterone, and triiodothyronine (T3) in shed skins of tegu lizards. We assessed whether hormone content of sheds varied across one year similar to what was previously detected in plasma samples. In addition, we aimed to identify the phase relationship between hormone levels of shed skin and plasma levels obtained from the same animals. High frequency of shedding occurred during the active season for tegus (spring/summer), while shedding ceased during hibernation (winter). All hormones measured in shed skins exhibited seasonal changes in concentration. Levels of testosterone in shed skins of male tegus correlated positively with plasma testosterone levels, while corticosterone in both males and females exhibited an inverse relationship between sample types for the same month of collection. An inverse relationship was found when accounting for a lag time of 3 and 4 months between sheds and plasma testosterone. These results indicate that endocrine content of sheds may be confounded by factors (i.e., seasons, environmental temperature, thermoregulatory behavior, among others) that affect frequency of molting, skin blood perfusion, and therefore hormone transfer from the bloodstream and deposition in sheds of squamates.
Keywords: Corticosterone; Hibernation; Non-invasive; Progesterone; Testosterone; Thyroid hormone